2015
DOI: 10.5152/tftrd.2015.91069
|View full text |Cite
|
Sign up to set email alerts
|

Intraligamentous Calcification of the Medial Collateral Ligament Mimicking Pellegrini-Stieda Syndrome in a Lower-Extremity Amputee

Abstract: Soft-tissue calcification is characterized by the accumulation of calcium in damaged collagen fibrils. The pathogenesis of calcium deposition is not fully understood. Inflammatory changes, trauma, and rheumatological diseases have been reported as possible risk factors. Pellegrini-Stieda syndrome (PSS) is post-traumatic calcification or ossification of the medial collateral ligament with a nonspecific etiology. It may occur after trauma or inflammation or it could be idiopathic. Here we present a case of postt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Chang et al [8] used both methods to portray the disease. Gokcen et al characterized the problem in a young guy who had knee disarticulation utilizing both X-ray and Ct/MRI scanning simultaneously in an interesting article [14]. A 46-year-old lady was the subject of a similar investigation by song et al Muschol et al found that a conventional knee X-ray was sufficient for identifying MCL calcification in the knee [9].…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al [8] used both methods to portray the disease. Gokcen et al characterized the problem in a young guy who had knee disarticulation utilizing both X-ray and Ct/MRI scanning simultaneously in an interesting article [14]. A 46-year-old lady was the subject of a similar investigation by song et al Muschol et al found that a conventional knee X-ray was sufficient for identifying MCL calcification in the knee [9].…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyapatite calcifications of the MCL are uncommon, and to the authors' knowledge, only 11 case reports have described calcification of the MCL [ 16 , 20 - 29 ]. Calcifications are thought to be caused by soft tissue hypoxia leading to fibrocartilaginous metaplasia, cellular necrosis, and deposition of hydroxyapatite crystals [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 "beak-like" Extends into the MCL Type 2 "tear-drop" Localizes within the MCL, but detached from the femoral condyle Type 3 "elongated" Above femur within the adductor magnus tendon Type 4 "beak-like" Extends into the MCL and adductor magnus tendon Hydroxyapatite calcifications of the MCL are uncommon, and to the authors' knowledge, only 11 case reports have described calcification of the MCL [16,[20][21][22][23][24][25][26][27][28][29]. Calcifications are thought to be caused by soft tissue hypoxia leading to fibrocartilaginous metaplasia, cellular necrosis, and deposition of hydroxyapatite crystals [20].…”
Section: Appearance: Locationmentioning
confidence: 99%
“…In an interesting report, Gokcen et al. described the condition using both X-ray and CT/MRI scanning simultaneously, in a young man who experienced knee disarticulation ( 14 ). Song et al.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al also depicted the condition using both technologies (4). In an interesting report, Gokcen et al described the condition using both X-ray and CT/MRI scanning simultaneously, in a young man who experienced knee disarticulation (14). Song et al carried out a similar study on a 46-year-old woman (6).…”
Section: Discussionmentioning
confidence: 99%